História do culto infantil e seu propósito na atualidade - Wischral Rodrigues, Marilze (Vox Scripturae - Revista Teológica Internacional, 2012)
The text presents historical research about the specific context of Christian education for childhood, through the times, from the Kinderpredigten at Martin Luther´s time, passing for the German Sonntagsschule, for the English and North American Sunday School, for the Kindergottesdienst that came to Brazil with the German Lutheran immigrants, at the beginning of century XIX, until the Infantile Cult of the current days, with the intention of supply the growth in the faith, as reply the redeemer action of God in the Baptism. This growth happens for the preaching of the gospel: announcement of the word and action of God for the person, for grace and mercy; for the intimacy relation: spirituality cultivated and express of cultic form; and for the experience of the faith: in the personal and communitarian scope, testifying the faith in concrete actions. It is a challenge today, to fortify the children’s worship for rediscovery of its function and intention; for the qualification of who works in it; for the deepening, contextualization of the faith contents; for the appropriation of creative and emancipating methodologies; for the creation of alternative forms to search the children who do not participate; for the awakening of the parents commitment; for the position of the church in retaking its priorities with the education in the Christian faith.
Keywords: Sunday School; Kindergottesdienst; Infantile Cult